PENGOLAHAN AIR LIMBAH DENGAN SISTEM REAKTOR BIOLOGIS PUTAR (ROTATING BIOLOGICAL CONTACTOR) DAN PARAMETER DISAIN - Said, Nusa Idaman (Center for Environmental Technology, 2005)
A rotating biological contactor (or RBC) is a type of fixed media filter which removes both organic matter and ammonia from water. Ã‚Â It can be added to a packaged plant for more efficient ammonia removal, replacing the aerator in both location and function.The RBC consists of a series of rotating discs. Ã‚Â These discs are coated with a biological slime like the slime on rocks in a healthy stream. Ã‚Â This slime is rotated through the air and and then through the wastewater so that it picks up oxygen in the air and breaks down B.O.D. in the wastewater. Ã‚Â Since the discs rotate through the air, there is no need to pump air into the wastewater. Ã‚Â And since the slime stays on the discs, there is no need to recycle sludge. The present study describes basic consideration of rotating biological contactor (RBC) system for wastewater treatment. The design of an RBC system must include the following consideration sach as organicsÃ‚Â and surface loading criteria, staging of RBC units, peripheral velocity, temperature, effluent characteritics and secondary clarifier. The RBC system have some advantages : smaller basin, less upset, high loading rate, nitrification/de-nitrification, high tolerance, low O&M Cost, durable constructions, odorless, no noise, and stable sludge characteristics.Ã‚Â Kata Kunci : Reaktor bioloigis putar, air limbah, parameter disain.